An analytical approach for control design of UPFC - Pandey R.K.; Singh N.K. (My University, 2025)
The paper presents an analytical approach for control design of Unified Power Flow Controller (UPFC) which functions as Power Oscillation Damping (POD) controller. Minimum Singular Value (MSV), Hankel Singular Value (HSV), Direct Component of Torque (DCT) and residue methods for finding most appropriate control input parameters of UPFC to damp power system oscillations has been widely studied. Studies reveal that identified control parameters of UPFC based on the above mentioned techniques provide adequate damping in power network with changing system conditions. The results presented are studied on single machine infinite bus power network which reflects suitability of this approach in tuning UPFC control parameters and also extendable to multi area systems. © 2008 IEEE.